Rare case of super-response to Cardiac Resynchronization Therapy in Macedonian patient with Dilated Left Ventricular Non-Compaction Cardiomyopathy - Shopov, Bozhin; Zafirovska, Planinka; Kostov, Jorgo; Manev, Nikola; Georgiev, Antonio (Valley International, 2024)
Background: Left ventricular non-compaction (LVNC) is rare cardiomyopathy with increased and prominent endomyocardial trabeculations also known as spongy myocardium. It is often found in association with a dilated cardiomyopathy (DCM) and has high incidence of Heart failure (HF). Cardiac resynchronization therapy (CRT) is currently recommended by the available guidelines for selected patients with Heart failure with reduced ejection fraction (HFrEF). Aim: Our case report aims to highlight the therapeutic benefits and superresponse to CRT in a patient with Left ventricular non-compaction cardiomyopathy and HFrEF. Case report: 55-year-old Macedonian male patient with HFrEF, Left bundle branch block (LBBB) remained symptomatic (NYHA III) despite optimal medical treatment (OMT). Echocardiography and CMR findings were in addition to dilated and left ventricular non-compaction cardiomyopathy. Cardiac resynchronization therapy was indicated and 18 months after implantation of CRT-P device we have achieved complete and utter reversibility of systolic myocardial function (EF from 23% to 53%), left ventricular internal diameter was reduced from 90mm to 64mm, left ventricular end systolic volume (LVESV) was reduced from 319ml to 98ml and patient quality of life significantly improved. Conclusion: Cardiac resynchronization therapy is a safe and valuable method of treatment for patients with HFrEF due to dilated left ventricular non-compaction cardiomyopathy.